Study about Branching Pattern of Dorsalis Pedis Artery with Clinical Significance - Hemamalini, .; Manjunatha , H. N. (Emerging Trends in Disease and Health Research Vol. 8, 2022)
The aim of the study was to see variations in the origin, course and branching pattern of the dorsalis pedis artery. Pulsations of the dorsalis pedis artery are frequently used to assess peripheral arterial disorders in the lower extremities, such as thromboangiitis obliterans (TAO) or Buerger's disease. The dorsalis pedis artery is a main arterial supply for the dorsum of the foot and is a direct continuation of the anterior tibial artery. However, because to the abundance of distal anastomoses around the ankle joint, arterial changes in the lower limbs are widespread. The absence of a dorsalis pedis arterial pulse does not always imply peripheral arterial illness, as it might be replaced by an expanded perforating branch of the peroneal artery, which may be missing or very thin and deviate laterally on the dorsum of the foot. During routine dissection of lower limbs for undergraduates we came across rare variations in the dorsalis pedis artery in its origin, course and branching pattern. In the present study, we also got another not described variation, that is, in the absence of arcuate artery the 2nd 3rd and 4th dorsal metatarsal arteries were arising from dorsalis pedis artery and not from the lateral tarsal artery. Normal anatomic description was found in 27 limbs. In 13 specimens we noted variations, includes bilateral anomalous origin of dorsalis pedis artery, bilateral lateral deviation of dorsalis pedis artery, double dorsalis pedis artery, trifurcation of dorsalis pedis artery and absence of arcuate artery. As variation in dorsalis pedis artery is quite common, it is essential to have a preoperative angiography for any abnormality, to prevent risks during surgical intervention.